ANALYSIS OF SCIENCE TEACHER BOOK CLASS VIII CURRICULUM 2013 - Lilis Farida; Wahida Agustina; Filka Janatin Kusna; Mochammad Yasir (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2021)
The purpose of this research was to analyze and examine the feasibility of the science teacher handbook for class VIII of the 2013 curriculum. The method used in this research is descriptive qualitative, namely by analyzing the 2013 curriculum teacher’s science book for class VIII Junior High School/Madrasah Tsanawiyah. The research was conducted on 22 December 2020-12 January 2021. The research site was at Trunojoyo Madura University, Kamal, Madura, East Java. The results showed that (1) the contents of the book were in accordance with the basic competency coverage, (2) the breadth, depth of present, and accuracy of the subject matter of each book had met the standards, (3) the books had shown examples of learning material factually, conceptually, and procedurally. in each chapter, (4) the contents of the book have the feasibility of learning activities in each chapter, and (5) the contents of the book meet the eligibility of the assessment. However, in chapter 8, namely the human respiratory system, respiratory disorders or diseases should be added about the corona virus.